Checklist of diatoms (Bacillariophyta) from Lake Ohrid and Lake Prespa (Macedonia), and their watersheds - Levkov, Zlatko; Williams, David M. (Phytotaxa, 2012)
A century of diatom research on Lakes Ohrid and Prespa (Macedonia) has yielded 900 different taxonomic entities including species, varieties and unidentified species. This checklist is based on a comprehensive compilation of diatom names sourced from all available published data. The intention is to provide a basis for future diatom research on these diverse ancient lakes and their watersheds. The checklist is organized around the classification in Round et al. (1990), with a few minor modifications.